Technological changes and cancer registries: an opportunity? (Italian Journal of Public Health, 2011)
Cancer registration has come a long way in the last 70 years. The basic function of a population based cancer registry is to record all new cases (of cancer) in a defined population (most frequently a geographical area) [1] and the core activity of a cancer registry is to generate statistics on the incidence of cancer, classified according to their site of origin and histology.
Keywords: cancer registry